VAMAS round‐robin study to evaluate a correction method for saturation effects in D‐SIMS. (7th May 2014) - Takano, Akio; Nonaka, Hidehiko; Homma, Yoshikazu; Tomita, Mitsuhiro; Murase, Atsushi; Hayashi, Syunichi; Barozzi, Mario; Kim, Kyung Joon; Sykes, David; Simons, David; Bennett, Joe; Magee, Charles W.; et al.
<x xml:space="preserve">Abstract</x> Recently, dynamic SIMS (D‐SIMS) is being used to analyze ions simultaneously over a wide range of concentrations, from matrix level to extremely low (ng g−1). However, D‐SIMS detectors, which are mostly used in pulse counting systems, have problems with detector saturation. Thus, the ion intensities of SIMS must be corrected in their high‐intensity region. It has been reported that the approximation intermediate extended dead‐time model (a‐IED model) can be used to correct saturated intensity in the higher region better than can the conventional model. In this study, we evaluated the usefulness of the a‐IED model to correct partially saturated and saturated intensities for magnetic‐sector‐type D‐SIMS and quadrupole‐type D‐SIMS for the effects of dead time. Nine organizations from five countries participated in this project. Analyzed specimens were an arsenic‐implanted silicon wafer and a diffused BN onto Si wafer. The instruments used to analyze arsenic‐implanted samples were five quadrupole‐type SIMS and four magnetic‐sector‐type SIMS. The instruments used to analyze the BN‐diffused samples were three quadrupole‐type SIMS, four magnetic‐sector‐type SIMS, and one time‐of‐flight‐type SIMS. We validated the usefulness of the a‐IED model to correct saturated intensities for all SIMS in this round‐robin test. The optimum extension parameter ρ tends to be affected by the ratio of the maximum reliable intensity to the maximum intensity. Copyright © 2014 John Wiley & Sons, Ltd.